De novo assembly of the zucchini genome reveals a whole‐genome duplication associated with the origin of the Cucurbita genus. Issue 6 (4th December 2017) - Montero‐Pau, Javier; Blanca, José; Bombarely, Aureliano; Ziarsolo, Peio; Esteras, Cristina; Martí‐Gómez, Carlos; Ferriol, María; Gómez, Pedro; Jamilena, Manuel; Mueller, Lukas; Picó, Belén; Cañizares, Joaquín
Summary: The Cucurbita genus (squashes, pumpkins and gourds) includes important domesticated species such as C. pepo, C. maxima and C. moschata . In this study, we present a high‐quality draft of the zucchini ( C. pepo ) genome. The assembly has a size of 263 Mb, a scaffold N50 of 1.8 Mb and 34 240 gene models. It includes 92% of the conserved BUSCO core gene set, and it is estimated to cover 93.0% of the genome. The genome is organized in 20 pseudomolecules that represent 81.4% of the assembly, and it is integrated with a genetic map of 7718 SNPs. Despite the small genome size, three independent lines of evidence support that the C. pepo genome is the result of a whole‐genome duplication: the topology of the gene family phylogenies, the karyotype organization and the distribution of 4DTv distances. Additionally, 40 transcriptomes of 12 species of the genus were assembled and analysed together with all the other published genomes of the Cucurbitaceae family. The duplication was detected in all the Cucurbita species analysed, including C. maxima and C. moschata, but not in the more distant cucurbits belonging to the Cucumis and Citrullus genera, and it is likely to have occurred 30 ± 4 Mya in the ancestral species that gave rise to the genus.